Can oral vitamin D prevent the cardiovascular diseases among migrants in Australia? Provider perspective using Markov modelling. (June 2015) - Ruwanpathirana, Thilanga; Owen, Alice; Renzaho, Andre MN; Zomer, Ella; Gambhir, Manoj; Reid, Christopher M
Summary The study was designed to model the effectiveness and cost effectiveness of oral Vitamin D supplementation as a primary prevention strategy for cardiovascular disease among a migrant population in Australia. It was carried out in the Community Health Service, Kensington, Melbourne. Best‐case scenario analysis using a Markov model was employed to look at the health care providers' perspective. Adult migrants who were vitamin D deficient and free from cardiovascular disease visiting the medical centre at least once during the period from 1 January 2010 to 31 December 2012 were included in the study. The blood pressure‐lowering effect of vitamin D was taken from a published meta‐analysis and applied in the Framingham 10 year cardiovascular risk algorithm (with and without oral vitamin D supplements) to generate the probabilities of cardiovascular events. A Markov decision model was used to estimate the provider costs associated with the events and treatments. Uncertainties were derived by Monte Carlo simulation. Vitamin D oral supplementation (1000 IU/day) for 10 years could potentially prevent 31 (interquartile range (IQR) 26 to 37) non‐fatal and 11 (IQR 10 to 15) fatal cardiovascular events in a migrant population of 10 000 assuming 100% compliance. The provider perspective incremental cost effectiveness per year of life saved was AU$3, 992 (IQR 583 to 8558). This study suggests subsidised supplementation of oral vitamin D may be a cost effective intervention to reduce non‐fatal and fatal cardiovascular outcomes in high‐risk migrant populations.